PRAKTEK PENGUASAAN PASAR OLEH PT SUMATERA RESOURCE INTERNATIONAL (SRI) TERHADAP HASIL GAMBIR DI KABUPATEN LIMA PULUH KOTA - Putra, Rian Dika; Jayakusuma, Zulfikar; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The practice of market control is prohibited in Article 19 of Law Number 5 of1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition.The practice carried out by PT Sumatra Resource International (SRI), which has marketcontrol, is to become the sole recipient of the supply of gambier products in LimapuluhKota Regency. This research was conducted to determine the form of market controlcarried out by PT SRI over gambier products in Limapuluh Kota Regency and todetermine the government's efforts to overcome the occurrence of monopolistic practicesby PT SRI This type of research uses empirical juridical research, in other wordssociological research or is called field research. The samples in the research were theDepartment of Industry and Manpower of Limapuluh Kota Regency, Public Relations ofPT SRI, Gambir Farmers and Middlemen in Limapuluh Kota Regency. The data sourceis primary data, through research instrument data collection with interviews, secondarydata consists of primary legal materials, secondary legal materials and tertiary legalmaterials. Sociological research data collection using interviews was analyzedqualitatively. In drawing conclusions the author uses an inductive thinking method,namely drawing specific conclusions into a general statement.Based on the research results, it can be concluded. First, PT SRI is the sole recipientof supplies and has market power over gambier produce in Lima Pulu Kota district, whichresults in price fluctuations, unilateral price determination and leads to weak gambierprices. Second, the Limapuluh Kota Regency government has made efforts to overcomethis problem. These efforts, such as the Warehouse Receipt System (SRG), are stillhampered by costs and plans to create regulations regarding standardization of pricesand quality of gambier to provide certainty in the price of gambier commodities.Keywords : Market Control, Anti-Monopoly, Business Competition, Unfair BusinessCompetition.